Experience with imidafenacin in the management of overactive bladder disorder. (February 2013) - Takeuchi, Takumi; Zaitsu, Masayoshi; Mikami, Koji
Overactive bladder (OAB) is a chronic syndrome defined by symptoms of urinary urgency with no underlying medical causes. First-line treatment of OAB comprises fluid intake advice and bladder training, supplemented by anticholinergic drugs if necessary. Owing to the chronic nature of OAB, the ideal anticholinergic treatment should have good long-term efficacy and tolerability. There are many anticholinergics available, although some of these are not specific for the bladder and can cause adverse effects such as dry mouth, constipation, blurred vision or cognitive impairment. Imidafenacin (a newer anticholinergic which has been marketed in Japan since 2007) was developed to improve the tolerability of anticholinergic therapy. This article summarizes the pharmacological properties, pharmacokinetics, clinical efficacy and tolerability of imidafenacin in the treatment of OAB. Data from key clinical studies of imidafenacin show that it has a fast onset of action and is effective for the treatment of OAB. It selectively binds to muscarinic receptors in the bladder and is associated with a good safety profile compared with other anticholinergics. The clinical efficacy, superior tolerability and adjustable dosing of imidafenacin make it a good anticholinergic for the treatment of OAB.